2022
DOI: 10.1021/acsnano.2c00471
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Polymer Bridging and Entanglement in Toughening Polymer-Infiltrated Nanoparticle Films

Abstract: Polymer-nanoparticle composite films (PNCFs) with high loadings of nanoparticles (NPs) (>50 vol %) have applications in multiple areas, and an understanding of their mechanical properties is essential for their broader use. The high-volume fraction and small size of the NPs lead to physical confinement of the polymers that can drastically change the properties of polymers relative to the bulk. We investigate the fracture behavior of a class of highly loaded PNCFs prepared by polymer infiltration into NP packin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…As shown in our previous work, 45 the fracture behavior of PINFs is strongly affected by the degree of confinement. To focus on the effect of polymer−NP interaction strength, we keep CR unchanged by selecting P2VP with a similar MW as PS and choosing NP packings with approximately the same pore size after silane passivation.…”
Section: Effect Of Polymer−np Interaction Strength On the Fracture To...supporting
confidence: 70%
See 3 more Smart Citations
“…As shown in our previous work, 45 the fracture behavior of PINFs is strongly affected by the degree of confinement. To focus on the effect of polymer−NP interaction strength, we keep CR unchanged by selecting P2VP with a similar MW as PS and choosing NP packings with approximately the same pore size after silane passivation.…”
Section: Effect Of Polymer−np Interaction Strength On the Fracture To...supporting
confidence: 70%
“…To estimate the degree of confinement, we define a CR as the ratio between the radius of gyration of the unperturbed polymer chain (R g ) to average pore radius (i.e., CR = R g /R pore ). 45 Our previous studies have shown that stronger interactions between polymer and NP as well as stronger confinement lead to a greater positive shift in T g (i.e., ΔT g = T g,confined − T g , bulk is positive) of the polymer in PINFs. 30,31,41,43,46 As shown in Figure 3, confined polymers exhibit higher-than-bulk T g for all the samples investigated.…”
Section: Effect Of Polymer−np Interaction Strength On Polymer Segment...mentioning
confidence: 92%
See 2 more Smart Citations
“…2,3 While past computational work and experiments have been focused on studying PNCs with nanofillers being the minority component, there is a push for engineering PNCs with larger nanofiller content (e.g., 450% by volume (%v) filler) as it has been found that the nanofiller-induced polymer confinement improves PNC toughness. 4,5 One approach to fabricate PNCs with higher filler content is through a solvent casting process whereby the nanofiller and polymer are mixed in the desired portions in a solvent, and upon solvent evaporation, one forms PNCs with the desired composition. [6][7][8] For such processes, there is a need to focus on polymer structure and dynamics around nanofillers in the presence of solvent and to study how the evaporation of the solvent affects the polymer structure and dynamics; the former is tackled in this paper.…”
Section: Introductionmentioning
confidence: 99%